The Territory as Infrastructure: The Case-Study of the Province of Rome. - Scoppetta, Cecilia (TeMA - Journal of Land Use, Mobility and Environment, 2012)
Even for the evident "similarities" with the results of scientific and technological evolution of the "network society", during the 90s the network metaphor has established itself as a dominant "image", to which link the understanding/interpretation (project) of the contemporary complexity (city/territory/society). This resulted in new descriptions/interpretations (projects) of the city and of the territory that move from the "material" and "immaterial" organization of the network itself. However, not always the "reduction" operated within planning was able to highlight limitations and contradictions inherent in the network metaphor as an interpretative key. In reality, the planning “speech” seems to focus primarily on "technical" issues – which certainly are not irrelevant – as congestion of flows, inadequacy of logistics platforms and, more generally, as regards the Italian case, on the serious and continuing infrastructure deficit: all factors that determine an undeniable impact on efficiency and competitiveness, on accessibility to services and on the timing of city use. But what, however, seems to be necessary is the overcoming of the still too sectoral approach towards a truly integrated planning pattern. This difficulty can be traced to some issues/problems of a structural nature that, historically, characterized the political-cultural and disciplinary Italian context. For example, despite the obvious consequences, measures regarding infrastructures tend to be made separately from the planning system. This is derived from the organization in different sectors that historically characterized public administration in general. In addition, we have particularistic logic of both vertical and horizontal type, that is the division of powers between administrative bodies of different levels or between structures of the same sector. This limits related to the issue of segmentation are more noticeable if you switch from ordinary activities to the field of territorial development policies, which are increasingly entrusted to local and regional dimension, in which tend to manifest ideas, proposals and initiatives. On the other hand, as regards the national infrastructure policies, the long absence of comprehensive planning documents, which can provide a reference for local authorities and economic operators, has been mirrored in an episodic and often contradictory action. This situation seems to persist despite the profound changes that, since the 90s, have invested "traditional” planning tools in the direction of greater institutional coordination, and despite the EU territorial policies. Thus, large territorial networks eventually take, at most, the role of (probable) elements of a "scenario" and not that of strategic development factors. An example of these difficulties is given by the recent territorial plan of the Province of Rome. The article suggests the assumption of the European strategic and multi-level (highly experimental) approach, based on the concept of “Territorial Platform”, towards the overcoming of the highlighted problems.